2005
DOI: 10.1007/s10811-005-3750-5
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites of Laminaria digitata tested in Lessonia nigrescens: Evaluation and improvement of cross amplification between kelps of two different families

Abstract: The use of primers designed originally to amplify DNA for one species in a different one can save time and resources, particularly for microsatellite loci. Microsatellite amplification improvements across two kelp families are reported, where loci originally described in Laminaria digitata (Laminariaceae) were tested in Lessonia nigrescens (Lessoniaceae). Amplification tests of 15 loci were successful for 12 cases. However, 11 of them presented multilocus banding profiles and only 1 was monolocus, but far from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The previous reports shows that the transferability of EST-SSRs from one species to another ranges from 40% to 89% (Liang et al, 2009). For seaweeds, the study of microsatellite cross-amplification between similar species has been reported in brown seaweeds and red seaweeds (Engel et al, 2003;Martínez et al, 2005).…”
Section: Cross-species Transferability Of Est-ssrmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous reports shows that the transferability of EST-SSRs from one species to another ranges from 40% to 89% (Liang et al, 2009). For seaweeds, the study of microsatellite cross-amplification between similar species has been reported in brown seaweeds and red seaweeds (Engel et al, 2003;Martínez et al, 2005).…”
Section: Cross-species Transferability Of Est-ssrmentioning
confidence: 99%
“…At present, SSRs have been utilized in genetic diversity analysis of seaweeds like red algae and brown algae (Kusumo et al, 2004;Martínez et al, 2005;Sun et al, 2006;Xie et al, 2009;Wang et al, 2011). However, little information is available regarding genetic variation of Ulva bloom algae with SSR markers to date except for Ulva intestinalis (Alström-Rapaport and Leskinen, 2002;Kostamo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%